Determinant Factors Influencing English Speaking Skill among Undergraduates: Challenges and Remedial Strategies - Monib, Wali Khan; Hadi, Hadi ur Rahman (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The exploration of factors affecting English-speaking skill remains a cornerstone in English language teaching research. However, a notable gap exists concerning the nuanced understanding of the affecting factors, especially within undergraduate contexts through the lens of Stephen Krashen's Second Language Acquisition Theory. This study explored the determinant factors influencing English-speaking skill among undergraduates studying English as a Foreign Language (EFL), using quantitative and qualitative approaches. By scrutinizing four essential domains – teacher and teaching-related aspects, curriculum and environmental factors, monitoring and linguistic, and affective and psychological factors – this research uncovers pivotal insights. The findings underscore that each of these factors significantly influences students’ speaking skill. The study highlights a need for active learning, authentic materials, and supportive environments to improve speaking skills. Furthermore, the findings indicate potential impediments of excessive grammar focus on fluency during spontaneous speech. Several strategies were unveiled to address the identified issues. The findings offer invaluable insights for educators, curriculum developers, and institutions regarding curriculum, teaching methods, and diverse strategies.